Implementation of Values Morality Through Learning Islamic Religious Education for Students at SDN 178 OKU - Azizah, Mufidatul; Salim, Hakimuddin; Mustofa, Triono Ali (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: Research This motivated by urgency formation character participant educate in the middle challenge moral degradation and dynamic changes of the times. Focus main studies This is Analysis How values Integrated Morals in a way System through eye Islamic Religious Education (PAI) lessons at SDN 178 OKU. Use company Qualitative [A] with method data collection through observation participatory, interview deep to informant key (PAI teachers and students), as well as documentation, research This dissect phenomenon formation character in a way holistic. Research results show that implementation mark Akhlakul Karimah at SDN 178 OKU was implemented through three main pillars: internalization mark towards the Creator (Hablu Minallah), interaction social and responsibility answer to environment (Hablu Minal Alam). Form concrete implementation includes a habituation program [Text unclear] like Dhuha prayer in congregation, tadarus Al-Qur'an with purification of tajweed, as well as integrate mark polite Al through 5S culture (Smile, Greet, Say Hello, Be Polite, Courteous). Findings field reveal that although school own visitbased faith and piety, still found challenge behavior student like violating regulations and conflict between participants students who need handling sustainable. Supporting factors main in the success of this program is exemplary behavior (Uswah Hasanah) from head schools and workforce educators, as well as synergy collaborative between party schools and parents. However, research this too • challenge significant, namely project allocation time eye PAI lessons are only two hours of lessons per week, which is considered No Valid For [Text unclear] aspect cognitive, affective, and psychomotor in a way in-depth. In addition, the inconsistency behavior from part individual power educator in give example concrete in the environment school become cone in the process of assimilation behavior students. This study in conclusion that coercion mark good morals require integrate curriculum that is not only based theory, but matter demonstration practical and environmental ecological supportive schools in a way consistent.